Determination of Extracellular Fluid Volume in Healthy and Azotemic Cats. (19th November 2014) - Finch, N.C.; Heiene, R.; Elliott, J.; Syme, H.M.; Peters, A.M.
<x xml:space="preserve">Abstract</x> Background Methods for determining extracellular fluid volume (ECFV) are important clinically for cats. Bromide dilution has been studied in cats to estimate ECFV. Markers of GFR also distribute in ECFV and can be used for its measurement. Hypothesis/Objectives The primary objective was to develop a method of determining ECFV from iohexol clearance in cats and evaluate agreement with that determined using bromide dilution. Additional objectives were to compare ECFV between azotemic and nonazotemic cats and evaluate appropriate methods of standardizing ECFV. Animals Client‐owned cats with varying renal function. Methods Validation of ECFV determined from slope‐intercept iohexol clearance was performed in 18 healthy nonazotemic cats. ECFV was then determined using the validated method and bromide dilution and agreement assessed. Appropriateness of standardization to body weight (BW) and body surface area (BSA) was evaluated. Results Extracellular fluid volume determined from slope‐intercept iohexol clearance and bromide dilution was 0.84 ± 0.32 L and 0.85 ± 0.19 L (mean ± SD), respectively. There were wide limits of agreement between the methods (−0.58 to 0.54 L) and therefore, agreement was considered to be poor. ECFV did not differ significantly between azotemic and nonazotemic cats (P = .177). BSA was found to be the best method for standardizing ECFV measurement in cats. Conclusions and Clinical Importance This study developed a method for determining ECFV from slope‐intercept iohexol clearance which provides simultaneous assessment of renal function and an estimate of ECFV. ECFV does not differ between azotemic and nonazotemic cats, which suggests fluid volume loss or overload is not an important clinical feature in cats with mild chronic kidney disease.